Penerapan Metode Dinamika Molekul untuk Pembelajaran: Konsep Titik Leleh dan Perubahan Wujud - Widiasih, Herawati, Heni Safitri, Artoto Arkundato (Jurnal Teori dan Aplikasi Fisika, 2013)
Molecular dynamics method has been applied to model the phase transition of the aluminium (Al). We used the LAMMPS molecular dynamics code to simulate the physical process of the phase transition and observing the dynamics of atoms by using Jmol vizualitation code. From the simulation data we found that the phase transition where the melting point of the material is, can be observed at temperature T = 1059,75 K. In this view we may use the molecular dynamics method as an innovative model of physical learning model in senior high school level, as an alternative of dry lab. Keywords: Molecular dynamics method, Phase transition, Melting point, LAMMPS.